Kajian Hubungan Komponen Beban Kerja Dengan Kinerja Perawat Pelaksana Di Ruang Rawat Inap Rumah Sakit Harapan Bunda Batam - Didi Yunaspi; Zulkarnain Edward; Emil Huriani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
In the inpatient room of the Harapan Bunda Batam hospital nurses complained of excessive workloads and the number of nurses that did not match the number of patients who had to be served. High workload will reduce nurse performance. A good nursing performance will create quality implementation of a quality nursing process. The purpose of this study was to determine the relationship of workload components with the performance of implementing nurses in the inpatient room at Harapan Bunda Hospital in Batam. Descriptive analytic research design,